Pengaruh Pembelajaran Kewirausahaan Terhadap Minat Menjadi Wirausahawan Pada Mahasiswa Program Studi S1 Pendidikan Ekonomi Angkatan 2018 - Trias A. Rahman; Usman Moonti; Radia Hafid; Melizubaida Mahmud; Ardianyah Ardianyah; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The present research aimed to determine the effect of entrepreneurship learning on students’ entrepreneurial interest in  the Bachelor’s Degree Program in Economics Education, Class of 2018. Moreover, this research employed a quantitative approach with a survey research method. The primary data were obtained by distributing questionnaires to students of the Bachelor’s Degree Program in Economics Education, Class of 2018, with a total sample of 41 respondents. In the meantime, the data analysis technique used was simple linear regression. The research finding denoted that entrepreneurial learning affected students’ entrepreneurial interest in the Bachelor’s Degree Program in Economics Education, Class of 2018. The effect of entrepreneurial learning on students’ entrepreneurial interest was 50.1%, while the remaining 49.9% were affected by variables that were not examined in this research.